Aracna Swan: espetacularidade, performance do feminino e subversão de gênero na técnica de pontas - MÊRCES, Cristiano Paiva (2021)
The current research approaches the drag queen spetacularity and pointe shoes technique subversion wich is restricted to feminine in classical ballet. The research objective is to analyze the drag queen Aracna Swan spetacularity, who has in her visuality and corporeity the reference of both swan and spider, to realize the transgression of pointe shoes utilization and to understand how gender roles are performed in ballet, as well as to present some ballet technique subversive exemples. Drag queen is unterstood through queer theory according to Judith Butler’s studies (2003), that percieves the drag queen gender ambiguity. This study theorical basis is Ethnoscenology, according to Bião (2009), therefore it looks at the phenomenon from spetacularity perspective, approaching concepts of altered state of body and conciousness. This is a qualitative research of autobiographical nature. In order to analyze the data, the performances’ rehearsals, preparation and action were described through photos, videos, besides my personal narratives about the connection between person and persona. Finally, the research determined drag queen as spetacular, because she organizes her actions in order to attract the viewr’s gaze; it’s a man in travesti who apropriates the pointe technique and subverts rules established long time ago, breaching to new ways to do/think dance.